DIVERSIFIKASI EKONOMI RUMAH TANGGA PADA DESA – DESA SEKITAR TAMAN NASIONAL KERINCI SEBLAT DI KABUPATEN LEBONG PROVINSI BENGKULU - Sukiyono, Ketut; Widiono, Septri; Apriyanto, Enggar (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
Economic diversity has often been promoted as a means to achieve the economic goal of stability. Many empirical studies have also concluded that greater diversification in economic can reduce vulnerability and engendering financial development. The objective of this paper is to analyze the degree of economic diversification at village level. This research was conducted at twenty villages located around Kerinci Seblat National Park (TNKS) and determined purposively and surveyed. Twenty households from each selected village were selected using systematic random sampling method, so the total respondents were 400 households. Economic diversity at the village level was estimated using EDI suggested by Dewi, et al (2005).Research found that EDI value for each village studied varies from 0.20 to 1.00 with no village reaches 1.099, which is an ideal condition. The lowest EDI, i.e. 0.20, occurs in the village of Karang Dapo Atas and Karang Dapo Bawah, subdistrict of Bingin Kuning and the village of Ujung Tanjung II Subdistrict Embong Uram Karang. This value indicates that households in the village surveyed simply rely on one type of work, especially in the agricultural sector. This also means that not many households get into other employment sectors such as mining and or services/stalls/stores. By simply relying on agriculture as its main source of income, households tend to be vulnerable if there is a change in the agricultural sector, especially in sectors such as coffee and rubber plantations.